Telemedicine in stroke patients during the COVID-19 pandemic: Literature Review - Pradani, Indra; Sulistyani, Sulistyani (Universitas 'Aisyiyah Yogyakarta, 2023)
The effectiveness of stroke therapy depends on speed, accuracy and a multidisciplinary approach. The era of the COVID-19 pandemic has caused a high risk of treatment for stroke patients. The application of telemedicine or telestroke that is good and focuses on quality is a possible alternative for stroke therapy during the COVID-19 pandemic. This study aims to determine the effectiveness of telemedicine in stroke patients during the COVID-19 pandemic. This study used a systematic review research design, namely by searching journal articles on Google Scholar, PubMed, and Research Gate databases, using keywords (